Propagation of Error and the Reliability of Global Air Temperature Projections - Frank, Patrick (Frontiers in Earth Science, 2019)
The reliability of general circulation climate model (GCM) global air temperature projections is evaluated for the first time, by way of propagation of model calibration error. An extensive series of demonstrations show that GCM air temperature projections are just linear extrapolations of fractional greenhouse gas (GHG) forcing. Linear projections are subject to linear propagation of error. A directly relevant GCM calibration metric is the annual average 12.1% error in long-wave cloud forcing (LWCF) produced within CMIP5 climate models. This error is strongly pair-wise correlated across models, implying a source in deficient theory. Climate model LWCF error introduces an annual average ±4 Wm-2 uncertainty into the simulated tropospheric thermal energy flux. This annual ±4 Wm-2 simulation uncertainty is 114 larger than the annual average ~0.035 Wm-2 change in tropospheric thermal energy flux produced by increasing GHG forcing since 1979. Tropospheric thermal energy flux is the determinant of global air temperature. Uncertainty in simulated tropospheric thermal energy flux imposes uncertainty on projected air temperature. Propagation of LWCF thermal energy flux error through the historically relevant 1988 projections of GISS Model II scenarios A, B, and C, the IPCC SRES scenarios CCC, B1, A1B, and A2, and the RCP scenarios of the 2013 IPCC Fifth Assessment Report, uncovers a ±15 C uncertainty in air temperature at the end of a centennial-scale projection. Analogously large but previously unrecognized uncertainties must therefore exist in all the past and present air temperature projections and hindcasts of even advanced climate models. The unavoidable conclusion is that an anthropogenic air temperature signal cannot have been, nor presently can be, evidenced in climate observables.